The deadly game : a British Army secret agent handler in the Troubles / Will Britten. - Britten, Will (The History Press, 2025)
South Armagh, Northern Ireland, 1983. Will Britten, 23, has just qualified as an agent handler for the British Army's ultra-secret Force Research Unit. He and a fellow agent handler complete the detailed paperwork following a covert meet with one of the Detachment's most important agents, who has successfully infiltrated 'Mad Dog' McGlinchey's INLA Active Service Unit. A few days later, there is a phone call. The draft Contact Form wasn't put in the burn bag. Both PIRA and INLA now know his real name. What would you do?